Konsep Rate of Profit dan Stabilitas Ekonomi Perbankan Syariah - Trisiladi Supriyanto (ETIKONOMI, 2015)
The Rate of Profit Concept and Economic Stability in Islamic BanksThis study aims to find the concept of rate of profit on Islamic banking that can create economic justice. Rate of profit that creates economic justice can be achieved through its role in maintaining the stability of the financial system in which there is an equitable distribution of income and wealth. To determine the role of the rate of profit as the basis of the sharing system implemented in the Islamic financial system, we can see the connection of rate of profit in creating financial stability, especially in the asset-liability management of financial institutions that generate a stable net income or the rate of profit that is not affected by the ups and downs of the market risk factors including indirect effect on interest rates. Futhermore, Islamic financial stability can be seen from the role of the rate of profit on the stability of the Islamic financial assets that are measured from the Islamic financial asset price volatilityDOI: 10.15408/etk.v14i2.2270